2022
DOI: 10.3390/ijms232314764
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Synthetic Approach on the Formation and Magnetic Properties of Iron-Based Nanophase in Branched Polyester Polyol Matrix

Abstract: This article shows the success of using the chemical reduction method, the polyol thermolytic process, the sonochemistry method, and the hybrid sonochemistry/polyol process method to design iron-based magnetically active composite nanomaterials in a hyperbranched polyester polyol matrix. Four samples were obtained and characterized by transmission and scanning electron microscopy, infrared spectroscopy and thermogravimetry. In all cases, the hyperbranched polymer is an excellent stabilizer of the iron and iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 89 publications
1
8
0
Order By: Relevance
“…Previously, in our studies, it was shown that hyperbranched polyester polyols are good stabilizers in the formation of composite nanoparticles of a number of biophilic metals (copper [40], iron [43], and cobalt [41]) via the chemical recovery method, using hydrazine hydrate or sodium borohydride as active reducing agents. Among the synthesized nanomaterials, superparamagnetic polyol-stabilized cobalt nanoparticles are of particular interest as they can be used as multifunctional nanocomposites for biomedicine, advanced technologies, and theranostics.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previously, in our studies, it was shown that hyperbranched polyester polyols are good stabilizers in the formation of composite nanoparticles of a number of biophilic metals (copper [40], iron [43], and cobalt [41]) via the chemical recovery method, using hydrazine hydrate or sodium borohydride as active reducing agents. Among the synthesized nanomaterials, superparamagnetic polyol-stabilized cobalt nanoparticles are of particular interest as they can be used as multifunctional nanocomposites for biomedicine, advanced technologies, and theranostics.…”
Section: Introductionmentioning
confidence: 89%
“…The temperature in the chamber was determined using a contact thermometer OMEGA HH804 (Engineering Inc., Norwalk, CT, USA) for all measurements. For the spectra fitting, the OriginPro program package was used; the Gauss function was used throughout [43].…”
Section: Equipmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase the statistical dose, the sample was pumped through the measuring chamber by using a piezoelectric dispenser. Each sample was detected sequentially six times; the recording time was sequential and amounted to 60 s. For processing the footage of the Nanosight instrument, NTA 2.3 software applications (build 0033) and OriginPro program package were used; the Gaussian function was used throughout, as described previously. , The detailed work is currently presented in the Principle of Operation by Carr and Malloy. , The hydrodynamic size meter ( D h ) was calculated with the measurement of the two-dimensional Einstein–Stokes equation …”
Section: Materials and Methodsmentioning
confidence: 99%
“…To increase the statistical dose, the sample was pumped through the measuring chamber using a piezoelectric dispenser. Each sample was detected sequentially 6 times; the total recording time was 60 s. For processing the footage from the Nanosight instrument, NTA 2.3 (build 0033) and OriginPro software were used; the Gauss function was employed as described previously [27,28]. The detailed procedures are described elsewhere [29,30].…”
Section: Equipmentmentioning
confidence: 99%